PENULIS DAN MAKNA PUISI ANAK DALAM HARIAN KOMPAS MINGGU* - Nurgiyantoro, Burhan (Diksi, 2006)
The view that poetry is one means of expressing various ideas, thoughts,and feelings applies on both adult poetry and poetry for children, which isnowadays increasingly written and published in, among others, magazines andnewspapers. Today such poetry is also written by children themselves. A study onsixty-five poems for children sampled from the Kompas daily Sunday editions of2005 has revealed that almost all of the poetry has been written by children, with3.1%, 78.5%, and 9.2% of them being, respectively, kindergarten, elementaryschool, and junior high school children (though another 9.2% of them areunidentifiable).The themes of the poems are quite various and all reflect the world ofchildren revealed through their point of view. However, there are certain recurringthemes: nature and the environment, parents and teachers, and animals, all ofwhich indicate children's closeness to them. Other themes also found are, amongothers, sports and toys, others' good deed, religiosity, money saving, and honesty.Generally the tone is didactic though the child writer means to invite or urge to dosomething. It indicates the children's innocence and directness of mind and way ofthinking. Their teachers at school or their parents at home often tell them directly todo something and they just re-express it in the same manner. In poetic aspects, anumber of the poems seem good enough but a part of the others still do not seem tobe already well processed, especially in terms of word choice.Keywords : children's literature, children's poetry, child writer, themes ofchildren's poetry